Breakdown by Streptomycin of Initiation Complexes Formed on Ribosomes of Escherichia coli - Modolell, Juan (1970)
Streptomycin induces breakdown of the completed 70S initiation complex on ribosomes of Escherichia coli, but it does not interfere with any step in the formation of the complex. Moreover, it does not appear to interact with the ribosome in any special way during initiation, since the kinetics of breakdown are the same whether streptomycin is added before formation of the initiation complex, or after its completion, or (as previously observed) after formation of a polypeptide. fMet-tRNA is released as such, without chain elongation; it is released from a puromycin-reactive („P”) site. Streptomycin thus appears to distort not only the A site of the ribosome (as suggested earlier) but also the P site.